COVID-19 associated acute transverse myelitis unresponsive to steroid therapy - Shafi, Mohammad Sameer; Shafi, Shahaan; Ghasemi, Reza; Vameghstahbanati, Motahareh (International Journal of Research in Medical Sciences, 2022)
A 63-year-old female presented to hospital with nausea, vomiting and abdominal pain. After primary evaluation, SARS-CoV-2 infection was suspected and confirmed via polymerase chain reaction (PCR) assay. She was started on broad spectrum antibiotics and remdesivir. After 12 days of hospitalization, she reported bilateral weakness and numbness of lower extremities and increased shortness of breath in the absence of fever. MRI with contrast was performed which showed intrinsic spinal cord lesion at the C7-T3 levels suggestive of transverse myelitis. She was started on IV steroids and was transferred to tertiary hospital for higher level of care. On neurological exam, there was an obvious reduction in the power of lower extremities and hyperreflexia was noted. Due to increasing weakness, MRI of cervical and thoracic spine was repeated and subsequently was started on Solu-Medrol 1-gram IV daily for 5 days. She was unresponsive to steroid therapy and refused plasmapheresis. Her course of hospitalization was complicated with acute on chronic renal failure and obstructive uropathy.